Examining the impact of physical education and physical skills development on preschoolers’ physical and mental health - Wang, Nina; Wang, Qinglei; Liu, Xiaohong; Mahfooz, Masood; Savila, Zubia (Frontiers in Psychology, 2023)
With socio-economic development and the popularization of scientific child-bearing philosophy, education has become the focus of the current society. The aim is to promote the physical & mental health of Preschoolers and improve their comprehensive learning ability. This work adopted the Questionnaire Survey (QS) and expert evaluation to scrutinize the impact of sports skills and physical education on preschoolers’ physical and mental health. To this end, it first expounded on the development of sports skills and the basic connotation of sports. Secondly, the characteristics of Preschoolers and the importance of preschool education were discussed. Finally, the physical & mental health of 60 Preschoolers was evaluated based on physical skill development and sports. The results showed that the respondent Preschoolers were grouped reasonably, and the research results had high reference values. In the control group, four Preschoolers’ physical conditions changed significantly in the best case. By comparison, in the experimental group, Preschoolers with significant physical changes had reached nine at best. On the other hand, as high as nine respondents had shown significant improvement in mental state in the best case. Therefore, physical skill development and physical education significantly impact Preschoolers’ physical & mental health, which has an important impact on Preschoolers’ learning. The finding provides a reference for Preschooler’s sports skills development and contributes to Preschoolers’ comprehensive physical education teaching.